2003
DOI: 10.1177/1077558703254101
|View full text |Cite
|
Sign up to set email alerts
|

Sicker and Poorer—The Consequences of Being Uninsured: A Review of the Research on the Relationship between Health Insurance, Medical Care Use, Health, Work, and Income

Abstract: Health services research conducted over the past 25 years makes a compelling case that having health insurance or using more medical care would improve the health of the uninsured. The literature's broad range of conditions, populations, and methods makes it difficult to derive a precise quantitative estimate of the effect of having health insurance on the uninsured's health. Some mortality studies imply that a 4% to 5% reduction in the uninsured's mortality is a lower bound; other studies suggest that the red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
292
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 416 publications
(305 citation statements)
references
References 126 publications
10
292
1
2
Order By: Relevance
“…3,10,11 In a review of the literature, Hadley 12 observed that the uninsured receive fewer preventive and diagnostic services, less therapeutic care, and tend to be more severely ill than their insured counterparts. The uninsured also are less likely to receive medical care when they develop symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…3,10,11 In a review of the literature, Hadley 12 observed that the uninsured receive fewer preventive and diagnostic services, less therapeutic care, and tend to be more severely ill than their insured counterparts. The uninsured also are less likely to receive medical care when they develop symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have showed the positive association of socioeconomic variables with the individuals intention to purchase health insurance (12)(13)(14). Several empirical studies cited education, income, family size, dependents and health status as variables which were significantly associated with health insurance purchase (15)(16)(17)(18)(19)(20)(21). Therefore, these variables were considered and grouped together while preparing a theoretical framework.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The consequences of being uninsured are well documented; compared with those who have health insurance, the uninsured more frequently go without needed medical care; receive lower quality care; and as a result, have worse health (Ayanian et al 2000;Ayanian et al 1993;Hadley 2003;Institute of Medicine 2001a, 2002aOsteen et al 1994;Roetzheim et al 1999). Being uninsured also poses serious fi nancial threats to Americans, with millions carrying a large burden of debt from medical expenses ( Himmelstein et al 2005).…”
mentioning
confidence: 99%